Exploring managers’ perceptions on sponsorship relations and decision making in the Malaysian B2B context - Mohamad-Noor Salehhuddin Sharipudin,; Nurzihan Hassim,; Suffian Hadi Ayub,; Fam, Kim-Shyan; Nusanee Meekaewkunchorn, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In a post-pandemic environment, businesses face new challenges in sustaining stakeholder interest due to the ever-changing consumer behaviour trends and a more fragmented media landscape. Achieving sponsorship contracts within this tumultuous financial period due to limited sponsor budget raises uncertainty in a potential or existing sponsorship relations due to competition with other organisations for the support of targeted sponsors. The objective of this study is to understand sponsorship relations and decision making from sponsors’ point of view and to explore approaches deployed by sponsored properties in drafting their proposals. In doing so, the study implemented semi-structured interviews with thirteen (13) corporate communication and marketing managers in Malaysia who were directly associated with sponsorship or sponsorship-seeking exercises through the marketing and branding programmes of their organisations. Through a thematic analysis, our study discovered three main findings on establishing sponsorship relations which included prioritising stakeholders, upholding current policies and developing value-added collaborations for growth. The need for accountability, compliance with organisation standards and linkages to government initiatives provided sponsored properties with the awareness of the evolving B2B sponsorship and media environment. The study emphasised the significance of ethical business practices when making strategic decisions on sponsorship. Further to this, the study outlined implications from the selection of sponsored properties in the business-to-business (B2B) community to continue fostering trust and inspire confidence from the public through strategic media and enduring partnerships.